Gaucher Disease: The Metabolic Defect, Pathophysiology, Phenotypes And Natural History - Baris, Hagit N. (Pediatr Endocrinol Rev, 2014)
Gaucher disease (GD), a prototype lysosomal storage disorder, results from inherited deficiency of lysosomal glucocerebrosidase due to biallelic mutations in GBA. The result is widespread accumulation of macrophages engorged with predominantly lysosomal glucocerebroside. A complex multisystem phenotype arises involving the liver, spleen, bone marrow and occasionally the lungs in type 1 Gaucher disease; in neuronopathic fulminant type 2 and chronic type 3 disease there is in addition progressive neurodegenerative disease. Manifestations of Gaucher disease type 1 (GD1) include hepatosplenomegaly, cytopenia, a complex pattern of bone involvement with avascular osteonecrosis (AVN), osteoporosis, fractures and lytic lesions. Enzyme replacement therapy became the standard of care in 1991, and this has transformed the natural history of GD1. This article reviews the clinical phenotypes of GD, diagnosis, pathophysiology and its natural history. A subsequent chapter discusses the treatment options.